Management of innovative development of urban areas - V. V. Merkulov; T. Yu. Shemyakina (Управление)
Concepts of «smart cities», development of innovative environment in territorial space, problems of formation of new environment due to increase in innovative activity, a tendency in approaches to innovative development of territories, characteristics for definition of city development are considered. The modern role of megalopolises as points of growth with which agglomeration (accession, concentration) represents process of the megalopolis creation is noted. The structure of agglomeration is formed by the cities, settlements, residential districts which don›t have clear physical boundary. The model of strategic management of the city based on the principles of system approach, integrity (definition of border and control system of all agglomeration), emerdzhenticy (achievement of synergetic effect), hierarchy (idea of orientation of the strategic analysis), self-organization (compliance to laws of the theory of organization) is investigated. The specifics of the innovative environment are defined by it ability to generate synergy, value added of elements from their interaction. The innovative environment is considered by the main source of creation of value added in the course of industrial production. New environments appear in new territories and result from association of factors of production: finance, work and raw materials in the production organization. Six key characteristics of the European approach to development of urban areas are selected - creative economy (smart economy), rational mobility (smart mobility), effective environmental management (smart environment), the educated population (smart people), a healthy lifestyle (smart living), the professional government (smart governance.) The status of «smart cities» is offered to be given to the cities of Russia after assessment on compliance to the accepted indicators of the Geneva Charter, the basic among other estimated indicator of territorial development it is necessary to accept the index of steady satisfaction of inhabitants of this territory.